Casey at the bat : a ballad of the Republic, sung in the year 1888 - Thayer, Ernest Lawrence, 1863-1940. (New York : Scholastic, 2001)
Text is presented as a "newly discovered," 100-year-old scrapbook into which newspaper articles, including Thayer's poem and other memorabilia, have been pasted, recording not only the events of the day--Casey's ninth-inning strikeout and the Mudville nine's four-to-two defeat--but also a broader view of the baseball world in 1888.
"Ernest Lawrence Thayer's Casey at the bat: a ballad of the Republic, sung in the year 1888, copiously and faithfully illustrated by Christopher Bing."--Front cover.
"Caldecott Honor book"
Keywords: Baseball -- Poetry; American poetry